Repellency of Carvacrol, Thymol, and Their Acetates against Imported Fire Ants - Pradeep Paudel; Farhan Mahmood Shah; Dileep Kumar Guddeti; Abbas Ali; Jian Chen; Ikhlas A. Khan; Xing-Cong Li (Insects, 2023)
In the United States, imported fire ants are commonly referred to as red imported fire ants (Solenopsis invicta Buren), black imported fire ants (S. richteri Forel), and hybrid imported fire ants (S. invicta × S. richteri). They are significant pests, and their control heavily relies on synthetic insecticides. The extensive use of insecticides has led to public concern about their potential negative effects on human health and the well-being of wildlife and the environment. As an alternative, plant-derived natural compounds, particularly essential oils (EOs) and their main constituents, show promise as safe and environmentally friendly products for controlling fire ants. Repellants are useful in managing fire ants, and plant-derived natural repellants may serve as a safer and more environmentally friendly option. This study investigates the repellency of EO-derived compounds carvacrol, thymol, and their acetates against imported fire ant workers. The results revealed that carvacrol, a GRAS compound (Generally Recognized As Safe), was the most potent repellent against S. invicta, S. richteri, and their hybrid, with minimum repellent effective doses (MREDs) of 0.98 µg/g, 7.80 µg/g, and 0.98 µg/g, respectively. Thymol also exhibited strong repellency, with MREDs of 31.25 µg/g, 31.25 µg/g, and 7.8 µg/g, respectively. Furthermore, thyme-red essential oil, characterized by a thymol chemotype containing 48.8% thymol and 5.1% carvacrol, was found to effectively repel the hybrid ants with an MRED of 15.6 µg/g. In contrast, thyme essential oil, characterized by a linalool chemotype lacking thymol and carvacrol, did not exhibit any repellent effect, even at the highest tested dose of 125 µg/g. This study provides the first evidence of the potent repellency of carvacrol and thymol against imported fire ant workers, indicating their potential as promising repellents for fire ant control.